2017
DOI: 10.1108/ir-11-2016-0281
|View full text |Cite
|
Sign up to set email alerts
|

Energy-efficiency hexapod walking robot for humanitarian demining

Abstract: Purpose The aim of this paper is to introduce a hexapod walking robot specifically designed for applications in humanitarian demining, intended to operate autonomously for several hours. To this end, the paper presents an experimental study for the evaluation of its energy efficiency. Design/methodology/approach First, the interest of using a walking robot for detection and localization of anti-personnel landmines is described, followed by the description of the mechanical system and the control architecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…As shown on the left of Figure 3, Hector Montes and Lisbeth Mena found that the power consumption of the robot is significantly affected by the load weight, which means that its transportation time is related to the load weight [43]. On this basis, we developed a function where load weight affects running time, as shown in the right side of Figure 3 and the Equation (1).…”
Section: Load Weight Influence Functionmentioning
confidence: 99%
“…As shown on the left of Figure 3, Hector Montes and Lisbeth Mena found that the power consumption of the robot is significantly affected by the load weight, which means that its transportation time is related to the load weight [43]. On this basis, we developed a function where load weight affects running time, as shown in the right side of Figure 3 and the Equation (1).…”
Section: Load Weight Influence Functionmentioning
confidence: 99%
“…During the stance phase, the trunk of the robot is moving forward. According to Equations (16), (22), and (34), in order to minimize the energy consumption, joint torques have to be as small as possible. Then, the first component of M, which is F x = Ma, have to be small.…”
Section: The Foot Trajectory Analysismentioning
confidence: 99%
“…In order to verify the energy model proposed in this paper, some experiments are carried out. Different from the electrical actuated robots [21,22], the energy consumption of a hydraulic actuated robot is obtained by the data of joint sensors. For SCalf, the position and force sensors mounted on the actuator (Figure 4) are used to measure the cylinder lengths c i and joint forces τ i (i = 1, 2).…”
Section: Validation Of the Energy Modelmentioning
confidence: 99%
“…Because of the difficulty of deploying technology within these constraints, a human with a metal detector has remained the primary method of mine clearance since the 1950s [9,12,27]. Even though safer methods such as machine [7,17], robotic [30,33] or animal clearance [6,8,29,34] are available, their use is not widespread because machines are expensive to maintain and are constrained by terrain, while animals are difficult to train and are practically suited only for specific clearance scenarios [13,17]. As of 2005, there were 48 manual mine clearance programs worldwide [9].…”
Section: Background On Humanitarian Deminingmentioning
confidence: 99%